Penerapan Media Jam Pecahan APK untuk Meningkatkan Pembelajaran Matematika di Sekolah Dasar - Rahmawanto, Roni (Jurnal Didaktika Pendidikan Dasar, 2018)
The research objective was to improve the fifth-grade children’s mathematics learning through APK Fraction Clock media at Ngentak Public Elementary School. APK is an Indonesian acronym for ‘Amati means Observation’, ‘Pahami means Understanding’, ‘Kreasi means Creation’. Prior observation showed that fifteen fifth-grade children encountered difficultyin learning mathematics in the academic year of 2017/2018. The end-semester examination result showed the mean score of mathematics = 38.87 which is categorized as low. A classroom action research was implemented using APK Fraction Clock media to improve mathematics learning. Learning materials were focused on equation, addition, and substraction in fraction. Data on children’s learning outcomes were collected  by administeriung an achievement  test. Whereas, learning activities were observed on pre-activity, whilst activity and post-activity. Data were analyzed in quantitatively and qualitatively. Results show that the minimum mastery level was improved from 57.67% to 78.33%. Moreover, the children’s learning activities were also improved. In conclusion, the use of APK Fraction Clock media was effective in improving the fifth-grade children’s learning activities and outcomes   at Ngentak Public Elementary School.